MODIFICATION METHOD OF STRAIN-LIFE CURVES UNDER DIFFERENT SURFACE CONDITIONS OF COMPONENTS (MT) - DUAN Heng; LIU PangLun; JIANG BingYan; SHE ShiQiang; LOU Rui (Jixie qiangdu)
Based on the practical problem of fatigue life prediction of landing gear, the fatigue life prediction model of landing gear components with surface treatment was studied. The calculation process of the traditional local stress-strain method was introduced, and the factors that affect the local stress-strain method for fatigue life prediction were systematically explained; The actual engineering research shows that the main factors for predicting the fatigue life of landing gear by using the local stress-strain method are surface treatment and surface roughness. By modifying the strain-life curve, a model for predicting the fatigue life of landing gear components is proposed. The two calculation examples show that the predicted results are in good agreement with the experimental results, and the proposed method for revising the strain-life curves under different surface conditions is reasonable.